2021
DOI: 10.1002/path.5638
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning detects genetic alterations in cancer histology generated by adversarial networks

Abstract: Deep learning can detect microsatellite instability (MSI) from routine histology images in colorectal cancer (CRC). However, ethical and legal barriers impede sharing of images and genetic data, hampering development of new algorithms for detection of MSI and other biomarkers. We hypothesized that histology images synthesized by conditional generative adversarial networks (CGANs) retain information about genetic alterations. To test this, we developed a ‘histology CGAN’ which was trained on 256 patients (train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…Therefore, future studies will likely rely on collaborations between multiple research centres to attain the level of performance and testing required to eventually enable safe and effective clinical decisions to be made based on molecular biomarkers detected through deep learning applied to histopathology slides. Additionally, Krause et al and Liu et al's use of synthetic images to augment digital pathology data sets has been shown to merit further research and such methods may prove invaluable in the future when assembling large, shareable data sets [27,41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, future studies will likely rely on collaborations between multiple research centres to attain the level of performance and testing required to eventually enable safe and effective clinical decisions to be made based on molecular biomarkers detected through deep learning applied to histopathology slides. Additionally, Krause et al and Liu et al's use of synthetic images to augment digital pathology data sets has been shown to merit further research and such methods may prove invaluable in the future when assembling large, shareable data sets [27,41].…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning models in digital pathology return predictions at the tile-level; therefore, it is necessary to implement a strategy of aggregating per-tile predictions in order to obtain a per-slide prediction. Methods of tile aggregation range from majority voting to MIL approaches [27,28].…”
Section: Transfer Learning and Tile Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Within unsupervised models, Generative Adversarial Networks (GANs) have been widely used in digital pathology, from nuclei segmentation [14], stain transformation and normalization [18,23], to high-quality tissue samples [12]. In addition, there has been some initial work on building representations of cells [5] or larger tissue patches [16].…”
Section: Introductionmentioning
confidence: 99%
“…One approach to reducing the time required to diagnose drug-sensitive mutation is the use of deep learning algorithms to provide a suggestion of mutations directly from tumor features. Several studies have addressed this issue of morphology–genotype correlation in cancers [ 1 , 2 , 3 , 4 , 5 , 6 ]. However, in these studies, researchers primarily focused on identifying the presence of specific mutations within carcinomas, without taking into account the knowledge that, in some circumstances, the mutational subtype, not merely the presence or absence of a mutation, is the main determinant of effective treatment.…”
Section: Introductionmentioning
confidence: 99%